2018
DOI: 10.1007/s11948-018-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

Balancing for an Effective Communication in Organizations

Abstract: Communication is an essential part of all activities of organizations. However, it is affected by technology. Today, email and social media are popular methods of communication in organizations. Each of the listed methods has advantages and disadvantages which will be discussed in this letter which tries to drive the attention of organizations to the need for a standard and balanced approach toward communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
1
7
0
1
Order By: Relevance
“…However, both the survey and the interview sessions reflected their full understanding of how learners should formulate academic and formal production in a polite and appropriate ways. This finding was consistent with the results of (Yousefi & Nassaji, 2021;Ton Nu, Murray, 2020;Touhidul & Sorooshian, 2019;Savic, 2018;Taguchi & Roever, 2017) who indicated learners' awareness of writing formal emails in an appropriate way, but their lack of English proficiency and pragmatic competence led them to write informal and impolite emails.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, both the survey and the interview sessions reflected their full understanding of how learners should formulate academic and formal production in a polite and appropriate ways. This finding was consistent with the results of (Yousefi & Nassaji, 2021;Ton Nu, Murray, 2020;Touhidul & Sorooshian, 2019;Savic, 2018;Taguchi & Roever, 2017) who indicated learners' awareness of writing formal emails in an appropriate way, but their lack of English proficiency and pragmatic competence led them to write informal and impolite emails.…”
Section: Discussionsupporting
confidence: 91%
“…One of the communicative ways that learners need to use is contacting through emails. In emails, the receivers usually expect to see formal and well-organized written emails that show the appropriate words and texts in relation to the cultures (Touhidul & Sorooshian, 2019). Students do not only need to learn the grammatical rules that help them improve their writing, but also, they "… need to know how report their thoughts into texts appropriately and accurately" (Imsa-ard, 2020, p. 36).…”
Section: Introductionmentioning
confidence: 99%
“…Effective communication is required in all types of businesses and today more than ever with the help of technology and media (Touhidul and Sorooshian 2019). According to Alyammahi et al (2020) communication is the fundamental tool in the workplace, hence the need for its effectiveness and balance in order to increase productivity with better decision making within an ethical culture consciously applied in everyday work.…”
Section: Effective Communicationmentioning
confidence: 99%
“…Ethics is a broad theme that coexists everywhere in life and in the business and administration, and which proves to be essential in all areas, including leadership (Bauman 2018;Kalshoven and Taylor 2018), teamwork (Alvi et al 2020;Lyubovnikova et al 2018), effective communication (Alyammahi et al 2020;Touhidul and Sorooshian 2019) and productivity (Ebert and Freibichler 2017;Tammany et al 2019). Therefore, this current research-which possesses a high degree of novelty while compared with other studies on similar topics, can be regarded as crucial given its main focus and, also, based on the research gap that was successfully identified, namely: the opportunity to describe the implication of ethics in leadership, teamwork, effective communication, and productivity, which includes the application of ethical values as university graduates assume the role of each of the mentioned dimensions of study in the organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Услед тога, за дисеминацију званичних пословних информација доминантан комуникациони канал у већини организација постаје имејл. Да би се избегле баријере дискретне комуникације и обезбедила ланчана дискусија у оквиру затворених група, друштвени медији су постали прилично популарни (Touhidul, Sorooshian, 2018). Употреба na вебу засноване и мобилне технологије, друштвени медији (Whatsapp, Telegram, Skype, Facebook) пружају платформу за интерактивни дијалог, али и могућност размене пословне документације и података у дигиталном формату (Baruah, 2012).…”
Section: нови пословни контекст -промене у комуникацији: нова платфорunclassified